AEROBIC BOXING TRAINING PROGRAM TO DEVELOP CERTAIN ASPECTS OF PHYSICAL FITNESS AMONG FEMALE TRAINEES IN GYMS - Mohammed, Noor Abd-alnaby (Universitas Negeri Jakarta, 2026)
Background. The research problem lies in need to investigate the effectiveness of a training method that combines motor continuity, time management, and variety in motor performance positions. Despite increasing prevalence of training programs within women's gyms, many of these programs still focus on general motor activity without precise guidance towards developing functional physical abilities related to efficiency of daily motor performance. Objectives. The study aimed to identify effect of an aerobic boxing training program on developing some elements of physical fitness among female trainees in gyms. Method. The researcher used the experimental method with a single group design with pre- and post-measurements. The research sample consisted of 10 female trainees practicing physical activity aged 24-26 years. The training program lasted 8 weeks with three training units per week. After applying tests under investigation and carrying out exercises prepared by the researcher. After conducting post-tests, results were statistically processed using Statistical Package System SPSS version 24. Results. Results showed statistically significant differences in favor of post-test in all variables, indicating effectiveness of aerobic boxing training in producing positive physical and motor adaptations in trainee. Conclusion. This study concluded that a training program using the air boxing method has proven effective in developing physical fitness components among the participants, reflecting the efficiency of this training method in improving overall physical performance in the gym. This contributes to developing the muscular endurance of the legs and arms, improving dynamic agility, and enhancing motor balance within a structured, applied framework.